(3OjhGf GdeGQOjfjs - (3eMeO Hf CHj HcQ Hf TQa GdeGQOGfj, YdGA GdOjfs
(3ChdgG (B:s
(3de jcf TjFkG ePchQkG aLQOJ Yf hSeg HeMh QSeg EP de CLO CgdkG dOjhGf LeYg HQSeg hCTQa HGSeg s
(3BNQgG (B:s
(3ef bUjOI QGFjI(B: (3Gddg jYWjc eG JQLhg ef CQH HLGg SjOfG GdoeNJGQ ef eVQ eMeO ef Edg GdYQT jPcQg HGdeOM aj eMce GdBjGJ hGdShQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQgG eY eLehY Chdg OjhGf GdeGQOjfj Uaj GdOjf GdMdj NWCs
(3cJH Ydi GdHWGbI GdeUhQI eY GdeLehYI(B: (3eLehY Chdg OjhGf Uaj GdOjf GdMdjs
(3hjHOh Cf GdagQSJ GdehLhO gh agQSJ OjhGf Uaj GdOjf GdMdjs
(3fSNI KGfjIs
(3hGdOjhGf ZjQ neQJH s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs